Satire and the Malaysian Law of Libel: Ummi Hafilda Bte Ali v Ketua Setiausaha Parti Islam Se Malaysia (PAS) & Ors - Nabi Baksh, Abdul Majid bin; Kwan, Rachel Elizabeth; Liddle, Margaret (Journal of Malaysian and Comparative Law, 2019)
Satire makes fun of its butt by exaggerating and distorting its features. This makes it liable to claims in defamation. By and large, the common law has not accepted, in such defamation claims, the defence that the work complained of was not a bunch of lies about the plaintiff but a satiric work out to poke fun at the persons or issues which engage the satirist. This is illustrated by the judgement in Ummi Hafilda Bte Ali v Ketua Setiausaha Parti Islam Se Malaysia (PAS) & Ors